Strategi Pemberdayaan Ternak Sapi di Desa Salam Kecamatan Patuk Kabupaten Gunungkidul Yogyakarta - Binarti, Floriberta (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Salam Village, Patuk District, Gunungkidul Regency, the Special Region of Yogyakarta Province, as the location of Kuliah Kerja Nyata Universitas Atma Jaya Yogyakarta period 81 Group 2 Unit A, has natural, agricultural and livestock potential. Livestock is the main goal of Salam Village, but its processing and marketing is still very conventional, which makes Salam Village less developed. This paper aims to present strategies of cattle empowerment from the waste processing into organic fertilizer and biogas to marketing techniques via online.